Реалізація технологічного прогресу на основі модифікованої версії моделі економічного зростання Р.М. Солоу: s-подібна крива виробництва, щo складається з n-кроків - Lopatin, Alexey (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2021)
The comparative analysis of the neoclassical Solow’s model and the modified Solow’s model in the implementation of technological progress has shown undeniable advantages of the modified Solow’s model. A modified version of the Solow’s economic growth model, based on an n-step production function in the form of n S-shaped functions for the implementation of technological progress, ensures the growth of the economy on a sufficiently large time interval comparable to the duration of the life cycle of the economy under study. In this interval, referred to as the “technology gap”, intensive output y (t) can be carried out according to the following options: monotonic decrease (stable 1-cycle) of the considered model; oscillations (stable n-cycles, n=2,4,16,…), “the economy marks time”; chaotic fluctuations. This result for the models of economic growth has not been described in the literature.